1998
DOI: 10.1007/bf02507163
|View full text |Cite
|
Sign up to set email alerts
|

Apoplast as the site of response to environmental signals

Abstract: When the life cycle of plants is influenced by various environmental signals, the mechanical properties of the cell wall are greatly changed. These signals also modify the levels and structure of the cell wall constituents and such modifications are supposed to be the cause of the changes in the wall mechanical properties. These changes in the cell wall, the major component of the apoplast, can be recognized as the response of plants to environmental signals. The analysis of the mechanism leading to the respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 116 publications
(89 citation statements)
references
References 122 publications
3
83
0
3
Order By: Relevance
“…The plant cell wall, which in the broadest sense comprises the extracellular matrix and apoplast milieu, represents the interface with the biotic and abiotic environment (Hoson, 1998;Sakurai, 1998;Lee et al, 2004). Accordingly, many developmental processes and induced plant responses have been identified that are directly or indirectly influenced by wall-localized molecular interactions and signalling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…The plant cell wall, which in the broadest sense comprises the extracellular matrix and apoplast milieu, represents the interface with the biotic and abiotic environment (Hoson, 1998;Sakurai, 1998;Lee et al, 2004). Accordingly, many developmental processes and induced plant responses have been identified that are directly or indirectly influenced by wall-localized molecular interactions and signalling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in most of the past experiments, plant seedlings were exposed to light continuously or temporally during cultivation. However, light is another factor that strongly influences the cell wall metabolism, thereby affecting elongation growth of seedlings 3) . Actually, light is recognized as one of gravity-substituting factors and so the effect of microgravity on growth may be diminished in the light.…”
Section: ) Discussionmentioning
confidence: 99%
“…It has been proposed that the cell wall plays an important role in resisting the gravitational force and supporting the plant's body on earth, as do the bones and muscles in an animal body (Hoson 1998). However, only limited information has been obtained for the mechanism of the anti-gravitational reactions in plants.…”
Section: Anti-gravitational System In Plantsmentioning
confidence: 99%